2017
DOI: 10.1021/acs.macromol.7b01930
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Nanodomains in Polyethylene Latexes

Abstract: Semi-crystalline polyethylene (PE) nanoparticles were obtained by free radical emulsion polymerization under mild conditions of pressure and temperature. At high surfactant concentration, the obtained anisotropic nanoparticles exhibit a strong degree of supercooling. This paper explores the relationship between the morphology of such particles and their high degree of supercooling. The shape anisotropy of the semi-crystalline PE particles already observed by transmission electron microscopy was confirmed by dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…[50] Previous works from our group showed that PE latex nanoparticles (obtained by conventional emulsion radical polymerization) did not crystallize at the temperature of the polymerization (70-80 8C) as a result of the nano-confinement of the PE chains but rather during cooling of the PE latex. [51] In our system, all of the previous analyses may not reflect the nano-organization during polymerization resulting from the PISA process. Indeed, the cooling of the reactor to recover the dispersions may be involved in the formation of the numerous morphologies observed very early in the reaction, by a kind of micellization (during polymerization) and crystallization (during cooling) process.…”
Section: Zuschriftenmentioning
confidence: 87%
See 1 more Smart Citation
“…[50] Previous works from our group showed that PE latex nanoparticles (obtained by conventional emulsion radical polymerization) did not crystallize at the temperature of the polymerization (70-80 8C) as a result of the nano-confinement of the PE chains but rather during cooling of the PE latex. [51] In our system, all of the previous analyses may not reflect the nano-organization during polymerization resulting from the PISA process. Indeed, the cooling of the reactor to recover the dispersions may be involved in the formation of the numerous morphologies observed very early in the reaction, by a kind of micellization (during polymerization) and crystallization (during cooling) process.…”
Section: Zuschriftenmentioning
confidence: 87%
“…Previous works from our group showed that PE latex nanoparticles (obtained by conventional emulsion radical polymerization) did not crystallize at the temperature of the polymerization (70–80 °C) as a result of the nano‐confinement of the PE chains but rather during cooling of the PE latex . In our system, all of the previous analyses may not reflect the nano‐organization during polymerization resulting from the PISA process.…”
Section: Methodsmentioning
confidence: 99%
“…We successfully undertook several studies based on this concept employing hydrophilic polymer chains obtained by reversible addition-fragmentation chain transfer (RAFT) and macromolecular design by interchange of xanthates (MADIX) in order to produce industrially relevant surfactant-free formulation for the production of film forming latex such as poly (meth)acrylics, [38][39][40][41] poly(vinylidene fluoride) 42 and poly(vinylidene chloride). [43][44][45] In the present paper, we apply this strategy for the first time to the emulsion copolymerization of ethylene and vinyl acetate for the production of VAE, building on our recent works on the polymerization of ethylene by free radical polymerization in water under mild conditions (i.e., temperature <90°C and ethylene pressure <250 bar), [46][47][48] and on PVAc 49,50 and polyethylene (PE) 51 particle synthesis mediated by macromolecular chain transfer agents (macroCTAs). The reactivity of these two monomers restricts the choice of potential macroCTAs to hydrophilic polymer chains carrying dithiocarbonate or dithiocarbamate end groups.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerizations can also be performed both in bulk and in aqueous emulsion [3][4][5][6][7][8][9][10][11]. Not only linear polymers but also nanocomposites have been prepared by the polymerization of ethylene in emulsion [12][13][14][15]. There have been many attempts to carry out radical ethylene polymerization under milder conditions (<100 • C and <1000 bar) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned aqueous emulsion polymerization of olefines applies a temperature above 80 • C, pressure around and above 200 bars, and high amounts of hardly removable surfactants [12][13][14][15][16]. Cyclodextrins (CDs) are widely used to complex and solubilize different hydrophobic substances, even monomers, and polymers [30][31][32].…”
Section: Introductionmentioning
confidence: 99%